Sex Differentiation and Early Gonadogenesis in Sebastes inermis Cuvier - Choi, Hee-Jung; Oh, Sung-Young; Myoung, Jung-Goo; Kim, Jong-Man; Hur, Jun-Wook; Park, Min-Ouk; Park, In-Seok (Ocean and polar research, 2008)
Early gonadal development and sexual differentiation of dark-banded rockfish (Sebastes inermis Cuvier) were followed from parturition to 400 days post parturition (dpp). During this period, average total length (TL) increased from 0.57 to 13.18 cm. Primordial germ cells (PGCs) were first detected at 0.68 cm TL (10 dpp). When fish reached 1.52 cm TL (50 dpp), initial stages of ovarian differentiation were identified by the presence of PGCs containing condensed chromatin and their transformation into meiotic oocytes. At 10.23 cm TL (300 dpp), the ovaries gradually developed into oocytes in the primary yolk stages. Ovary growth was rapid after sex differentiation, but testis tissue continued to multiply without growing until fish reached 6.97 cm TL (200 dpp), after which the production of spermatocytes, spermatogonia, and cyst cells was apparent. Histological analysis of gonadal structure suggested a gonochoristic sexual development pathway. Our analysis of the sex ratio at 400 dpp showed a significantly higher proportion of males.